PREVALENCE AND RISK FACTOR OF FELINE PANLEUKOPENIA VIRUS INFECTION IN CATS AT ARCLINIC PET CARE BOGOR - Hanafiah, Kayla Zahrah; Siagian, Tetty Barunawati (Buletin Veteriner Udayana, 2026)
Cat ownership in Indonesia has continued to increase over recent years, leading to greater awareness of pet health and veterinary care. One of the most common infectious diseases affecting cats is feline panleukopenia, caused by the Feline Panleukopenia Virus (FPV). FPV is a highly contagious disease associated with high morbidity and mortality rates, particularly in kittens and young cats. This study aimed to determine the prevalence of FPV infection and identify associated risk factors among cats examined at ArClinic Pet Care, Bogor, between January and September 2025. Medical records from this period identified 44 cats confirmed positive for FPV based on clinical examination, rapid antigen testing, and hematological analysis. The prevalence of FPV infection was 2.21%, indicating a relatively low occurrence during the study period. Chi-square analysis revealed that season (p < 0.05), age (p < 0.05), breed (p < 0.05), and vaccination status (p < 0.05) were significantly associated with FPV infection, whereas sex showed no significant association (p > 0.05). These findings highlight the importance of vaccination as the primary preventive measure against FPV and underscore the need for enhanced preventive efforts targeting young cats and domestic breeds, particularly during the rainy season when the risk of viral transmission is higher.